KILKA UWAG O WŁASNOŚCI (NA MARGINESIE BADAŃ NAD NADUŻYCIEM PRAWA W RZYMSKIM PRAWIE PRYWATNYM) - Longchamps de Bérier, Franciszek (Zeszyty Prawnicze, 2017)
Remarks on the Ownership (Aside-note to the Studies on the Abuse of Rights in Roman Private Law) Summary In the inter war period in the jurisdiction of the Polish Supreme Court based on BGB one could observe a relatively free approach to § 226 BGB. The judges most probably noticed the deficiencies of this provision. The analysis made in this paper shows that the primary problem lies in the views regarding the legal character of the ownership at various stages of the history of Rome. Up to now the disputes have been concentrated on the scope of the owner’s rights. The choices made by particular participants in such a fundamental matter have conditioned their analysis of the neighbourly relations and of the abuse of rights. However, the Roman sources do not present the rights of owners as unlimited. And in order to defend the individualistic or even absolute character of the ownership, it would be necessary to argue for the existence of a timeless notion of the ownership. Both arise more than significant objections.